Analisis Pengaruh Harga, Kualitas Produk Dan Iklan Terhadap Brand Image Dan Keputusan Pembelian Sepeda Motor Merek Kawasaki - Noerchoidah Noerchoidah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2013)
In the marketing and development of a product, the company must have a quality product, price and product positioning in the market place through the promotion, which in turn will affect the image barand and purchasing decisions. The transfer of a highly competitive business paradigm, companies are required to always be creative and innovative to get survive. The research data obtained through questionnaires and analyzed using Structural Equation Modeling (SEM) analysis techniques. To perform this analysis technique, there are seven steps that must be done, which is extended on the basis of theoretical models, extended flowcharts, workflow diagrams the conversion into equity, selecting the input matrices and estimation techniques, printing identification problem, evaluating criteria of goodness of fit and the interpretation and modification of the model. The full fit modeling results received using the technique of SEM analysis and tested the hypothesis that the quality of the product known influence on purchase decisions, promotional intensity influence on purchase decisions, affect the perceived price band image and purchasing decisions. Based on the results of the study, there are several managerial implications that can be used as a review. To improve the brand image and purchase decisions may be done by improving product quality, competitive prices and promotions.